Plasma- An Environment Friendly Technology - Ohlan, Rahul (International Journal of Computer Sciences and Engineering, 2019)
Plasma is one of the fastest emerging technologies conquering the world. It is a state of matter where atoms and molecules are electrically charged. Cold plasma is playing a very important role in almost all the fields of technology. It has witnessing the growth in scientific and industrial areas. It has extraordinary potential because of its rare characteristics such as flexibility capability and formation of new product. In addition to it plasma technology is environment friendly and saves allot of energy, due to which it finds its application in various fields. Plasma technology has emerged out as a great way of managing the waste. In this paper a detailed study is being done on plasma technology and its applications. This paper also gives an overview of various discharge sources and application. In this paper a deep analysis on cold plasma (non thermal plasma) is provided.